Correlation between the leg muscle strength, arm muscle power, hand-eye coordination, arm length, and body balance towards the accuracy of volleyball overhead passing of players from PBV pervas Sleman - Muhammad Khanif Hidayatulloh; Syamsuryadin, Syamsuryadin; Afni Silvia Putri; Alissa Rachel Chrystalin; Andrean Danu Wardana; Yoga Sampurna; Putri Ratu Rima; Mohammad Rizqi Febrian; Teresa Agustin Ababil; Bayu Akbar Prasetyo; Muhammad Rifqi Asyraf (Jorpres (Jurnal Olahraga Prestasi), 2025)
This research seeks to (1) ascertain the correlation between leg strength and the accuracy of volleyball overhead passes of players at Pervas Volleyball Club, (2) investigate the correlation between arm muscle strength and the accuracy of volleyball overhead passes of players at Pervas club, (3) investigate the correlation between hand-eye coordination and the accuracy of volleyball overhead passes of players at Pervas Club, (4) investigate the correlation between arm length and the accuracy of volleyball overhead passes of players at Pervas Club, (5) examine the correlation between body balance and the accuracy of volleyball overhead passes of players at Pervas club, and (6) examine the correlation among leg muscle strength, arm muscle strength, hand-eye coordination, arm length, and body balance concerning the accuracy of volleyball overhead passes of players at Pervas club. This research was a descriptive quantitative study employing a correlational methodology. The research population consisted of volleyball athletes of Pervas Club. The sample method employed purposive sampling. The criteria included: (1) male and female volleyball players from PBV Pervas Sleman Club, (2) aged 17 years old, and (3) were prepared to serve as a research sample. The leg muscle strength was assessed by using the wall sit test, arm muscle strength was evaluated by using the push-up test, handeye coordination was measured with the tennis ball throw-catch test, arm length was determined via the arm span test, and balance was tested by using the stork stand test. This research employed descriptive analysis, hypothesis testing, and determination testing as data analytic methodologies. The research findings indicate a correlation between leg muscle strength and passing accuracy, with a computed r value of 0.804. R table: 0.282, significance value: 0.000, which is less than 0.05. (2) A correlation exists between arm muscle strength and passing accuracy, with a computed r value of 0.948. R table: 0.282, significance value: 0.000, which is less than 0.05. (3) A correlation exists between handeye coordination and passing accuracy, with a calculated r value of 0.931. R table: 0.282, significance value: 0.000, less than 0.05. A correlation exists between arm length and passing accuracy, with an estimated r value of 0.932. R table: 0.282, significance value: 0.000, which is less than 0.05. (5) A correlation exists between body balance and passing accuracy, with a calculated r value of 0.986. R table: 0.282, significance value: 0.000, which is less than 0.05. (6) A correlation exists among leg muscle strength, arm muscle strength, hand-eye coordination, arm length, and body balance, with the accuracy of volleyball overhead passing at PBV Pervas Sleman Club, shown by a calculated F value of 1566. F value of 2.55 and significance level of 0.000, which is less than 0.05.